2011
DOI: 10.1111/j.1365-2249.2011.04369.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of natural killer T cells by α-carba-GalCer (RCAI-56), a novel synthetic glycolipid ligand, suppresses murine collagen-induced arthritis

Abstract: SummaryAlpha-carba-GalCer (RCAI-56), a novel synthetic analogue of agalactosylceramide (a-GalCer), stimulates invariant natural killer T (NK T) cells to produce interferon (IFN)-g. IFN-g exhibits immunoregulatory properties in autoimmune diseases by suppressing T helper (Th)-17 cell differentiation and inducing regulatory T cells and apoptosis of autoreactive T cells. Here, we investigated the protective effects of a-carba-GalCer on collageninduced arthritis (CIA) in mice. First, we confirmed that a-carba-GalC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
(69 reference statements)
1
16
0
1
Order By: Relevance
“…Kaieda et al showed that SGL-S23, an analog of α-GalCer, had suppressive effect on K/BxN serum transfer arthritis through IFN-γ [26]. We previously showed that α-carba-GalCer, an analog of α-GalCer, suppressed the severity of CIA through the induction of Th1-biased differentiation of CD4+ T cells [20]. In contrast to these studies, α-GalCer suppressed both Th1 and Th17 CD4+ T cells in GPI peptide-induced arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaieda et al showed that SGL-S23, an analog of α-GalCer, had suppressive effect on K/BxN serum transfer arthritis through IFN-γ [26]. We previously showed that α-carba-GalCer, an analog of α-GalCer, suppressed the severity of CIA through the induction of Th1-biased differentiation of CD4+ T cells [20]. In contrast to these studies, α-GalCer suppressed both Th1 and Th17 CD4+ T cells in GPI peptide-induced arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The draining lymph nodes (dLN) and splenocytes were isolated as described previously [20]. Single-cell suspensions were prepared in Roswell Park Memorial Institute (RPMI) 1640 medium (Sigma-Aldrich) containing 10% fetal bovine serum (FBS), penicillin–streptomycin (100 U/ml), 10 mM HEPES buffer solution (Gibco BRL, Grand Island, NY), 0.1 mM MEM nonessential amino acids (Gibco), 1 mM sodium pyruvate (Gibco), and 5.5 mM 2-mercaptoethanol (2-ME).…”
Section: Methodsmentioning
confidence: 99%
“…As the inhibitory and stimulatory actions of the NKT cells are better understood, interventions can be developed that modulate their effects in a favorable, disease-specific fashion [289][290][291].…”
Section: Natural Killer T (Nkt) Cellsmentioning
confidence: 99%
“…As early as day 3, DLN cells expressed reduced IL-6 and IL23p19 with unchanged TGF-ϐ while CD1d-tetramer + iNKT cells produced higher IFN-in spleen, liver and DLN. On day 10, DLN T cells stimulated with PMA and ionomycin showed polarisation towards Th1 and suppression of Th17 cell differentiation, in keeping with protective Th1 deviation during the initiation phase of CIA (Yoshiga et al, 2011).…”
Section: Manipulating Inkt Cells For Clinical Benefitmentioning
confidence: 99%